Toward Cold War thinking: editorial reactions to Churchill's iron curtain speech in North Carolina newspapers. (1st October 2016) - Levering, Ralph B.
Abstract : This article argues that the Cold War arrived in America – in Washington and in U.S. public opinion – between October 1945 and March 1947, and more specifically in February and March 1946. It also contends that Winston Churchill's 'iron curtain' speech on 5 March 1946 played an important role in alerting the American public to the reality that Soviet foreign policy was both expansionist and anti-democratic. Churchill's anti-Soviet speech, together with earlier 'firm' but more guarded speeches by Senator Arthur Vandenberg and Secretary of State James Byrnes, clearly contributed to the anti-Soviet milieu that was reflected in a Gallup poll in mid-March in which only 7% of respondents approved of 'the policy Russia is following in world affairs'. Ironically given the lasting fame of Churchill's speech, editorials in the five North Carolina newspapers analyzed in the article opposed what they saw as his main proposal: an Anglo-American alliance against Russia. Yet four of the five papers agreed with Vandenberg, Byrnes, and Churchill that Western nations needed to oppose Soviet expansionism firmly, thus upholding the ideals of the United Nations. The article concludes by explaining why President Harry Truman did not follow Churchill's lead in publicly condemning Soviet foreign policy for another year, until his famous 'Truman Doctrine' speech on 12 March 1947.